Pengaruh Waktu Aerasi terhadap Peningkatan Efisiensi Penghilangan Amonia di Air Lindi pada Sistem Ammonia Stripper - Fahrianto, Teguh; Naswir, Muhammad; Jalius, Jalius (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Talang Gulo Final Disposal Site (FDS) has a Leachate Treatment Plant (LTP) equipped with denitrification and nitrification facilities which function to reduce the concentration of ammonia (NH3) in leachate according to predetermined environmental quality standards. Research samples were taken in the form of leachate using the grab sampling method in accordance with SNI 6989.59:2008. The results of the research showed that the aeration time for the ammonia stripper of 3 hours, 6 hours and 12 hours both gave the highest value for the ammonia stripper efficiency percentage variable. The highest ammonia removal efficiency is aeration time of 12 hours. However, if we look at the operating efficiency of the ammonia stripper, the removal of ammonia by using an aeration time of 12 hours does not provide a significant improvement when compared to a treatment with an aeration time of 6 hours. This means that the operating time is 6 hours faster, the 6 hour variation can provide an ammonia removal efficiency of more than 90%